Obliquely‐arranged double skin paddles: A novel design to reconstruct extensive head and neck defects with a single fibula or peroneal flap - Lin, Ying‐Sheng; Liu, Wen‐Chung; Wang, Kuan‐Ying; Lin, Yaoh‐Shiang; Yang, Kuo‐Chung (Microsurgery, 2019)
Objective To reconstruct extensive head and neck defects usually necessitates double free flaps, which require a time‐and‐manpower‐consuming surgical procedure. We present using a single fibula or peroneal flap with the novel design of obliquely‐arranged double skin paddles to reconstruct an extensive head and neck defect. Methods From 1998 to 2016, eight patients with the age of 52.25 (35–71) years old had extensive head and neck defects after oral cancer ablation. All of the defects were through and through with the size of 16.25 (12–24) cm × 8.8 (4.5–11) cm. Six of the defects were due to buccal cancer. One was due to tongue cancer, and another one was due to gingiva cancer. All the defects were reconstructed with obliquely‐arranged double‐paddle free fibula or peroneal flaps. The long axis of the skin paddles was arranged at certain angle (30–45 degrees) to the long axis of lower leg, and the two separate skin paddles were used as the form of island flaps by isolating the cutaneous perforators to create a true chimeric flap. Results The skin paddle sizes were 14 cm × 3 cm–24 cm × 11 cm and 9.5 cm × 4.5 cm–13 cm × 8 cm. The average length of harvested fibula was 19 (10–30) cm. All of the eight flaps survived without obvious donor site morbidity. One patient had partial skin necrosis over recipient site, requiring surgical debridements and closure. One patient had superficial necrosis over the edge of outer skin paddle, which healed spontaneously. After the follow‐up periods of 1 month to 3 year and 8 months, two patients died of sepsis. Six of them could resume soft diet and had no saliva drooling. The remaining two remained nasogastric diet and had saliva drooling. Conclusion With the design of obliquely‐arranged double paddles, we may maximize the harvested skin area of lateral lower leg to reconstruct an extensive head and neck defect with a single free flap.